2015
DOI: 10.1021/acs.inorgchem.5b01002
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Metal–Dinitrogen Keggin-Type Polyoxometalate Complexes [PW11O39MIIN2)]5– (M = Ru, Os, Re, Ir): Bonding Nature and Dinitrogen Splitting

Abstract: Molecular geometry, electronic structure, and metal-dinitrogen bonding nature of a series of metal-dinitrogen derivatives of Keggin-type polyoxometalates (POMs) [PW11O39M(II)N2)](5-) (M = Ru, Os, Re, Ir) have been studied by using a density functional theory (DFT) method with the M06L functional. Among these Keggin-type POM complexes, Os- and Re-substituted POM complexes are the most active for N2 adsorption with considerable adsorption energy. The electronic structure analysis shows that Os(II) and Re(II) cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The transition metal center is stabilized by four O b atoms coming from the surface oxygen of Keggin-type POM ligand (see Figure b). Due to the very large distance between metal and O a atoms, the M–O a interaction can be viewed as a weakened bonding interaction, which provides a unsaturated metal atom in the pseudo-octahedral coordinated sphere. ,, Thus, the transition metal center has an additional ability to bind to a NO molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The transition metal center is stabilized by four O b atoms coming from the surface oxygen of Keggin-type POM ligand (see Figure b). Due to the very large distance between metal and O a atoms, the M–O a interaction can be viewed as a weakened bonding interaction, which provides a unsaturated metal atom in the pseudo-octahedral coordinated sphere. ,, Thus, the transition metal center has an additional ability to bind to a NO molecule.…”
Section: Resultsmentioning
confidence: 99%
“…of POMs was validated in our previous work. [ 66 ] The LANL2DZ pseudopotential was used for metal atoms. The 6‐31G(d) basis set was used for the main‐group atoms.…”
Section: Computational Model and Detailsmentioning
confidence: 99%
“…These findings supported that a dimeric Keggin-type POM derivative of rhenium could represent the intermediate that undergoes N–N bond scission with a moderate barrier. 57 In another case, we further investigate the possible reaction mechanism of a series of mono-transition-metal-substituted Keggin-type POM–dinitrogen complexes [PW 11 O 39 M(N 2 )] n− (M = Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Tc, Ru, Rh, Pd, Ag, Cd, W, Re, Os, Ir, Pt, Au, and Hg) for the NRR, in which the mono-lacunary Keggin-type POM ligand with five oxygen donor atoms serves as a strong electron donor to the metal center for the activation of the N 2 molecule. Our DFT results also indicated that Mo II –, Tc II –, W II –, Re II –, Ru II –, and Os II –POM complexes are significant for the binding and activation of an inert N 2 molecule.…”
Section: Introductionmentioning
confidence: 99%